2009
DOI: 10.1111/j.1528-1167.2008.01948.x
|View full text |Cite
|
Sign up to set email alerts
|

Magnetic resonance spectroscopy reveals an epileptic network in juvenile myoclonic epilepsy

Abstract: Summary Purpose:  To investigate the cerebral metabolic differences between patients with juvenile myoclonic epilepsy (JME) and normal controls and to evaluate to what extent these metabolic alterations reflect involvement of an epileptic network. Methods:  Sixty patients with JME were submitted to multi‐voxel proton spectroscopy (1H‐MRS) at 1.5 T over medial prefrontal cortex (MPC), primary motor cortex (PMC), thalamus, striatum, posterior cingulate gyrus (PCG), and insular, parietal, and occipital cortices. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
61
1
3

Year Published

2010
2010
2015
2015

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 75 publications
(73 citation statements)
references
References 40 publications
8
61
1
3
Order By: Relevance
“…This may partly be attributed to restrictions imposed by the single voxel size used in our analysis. In addition to recent data suggesting neurochemical dysfunction in different brain areas in patients with JME [6], we found evidence of metabolic disturbances in the hippocampi of our patients. Moreover, our data further corroborate the hypothesis that focal brain regions in patients with "predominantly generalized" epilepsy are more innately epileptogenic than controls [15].…”
Section: Discussionsupporting
confidence: 41%
See 1 more Smart Citation
“…This may partly be attributed to restrictions imposed by the single voxel size used in our analysis. In addition to recent data suggesting neurochemical dysfunction in different brain areas in patients with JME [6], we found evidence of metabolic disturbances in the hippocampi of our patients. Moreover, our data further corroborate the hypothesis that focal brain regions in patients with "predominantly generalized" epilepsy are more innately epileptogenic than controls [15].…”
Section: Discussionsupporting
confidence: 41%
“…However, there is a consistent body of data that has accumulated with the advancement of neuroimaging techniques that challenge the current hypothesis of JME as a condition with no anatomic substrate. A magnetic resonance spectroscopy (MRS) study in patients with JME gave evidence for a specific network of neurochemical dysfunction affecting particular brain structures including primary motor and medial prefrontal cortex and thalamus [6]. Furthermore, serotonin 1A receptor binding potential (BP) measured with positron emission tomography (PET) revealed reduction in dorsolateral prefrontal cortex, raphe nuclei and hippocampus that is not related to atrophy [7].…”
Section: Introductionmentioning
confidence: 99%
“…A more recent study investigating a large network of regions implicated in JME using MRS, including the medial prefrontal cortex, primary motor cortex, occipital cortex, and posterior cingulate cortex, further demonstrated decreased NAA in primary motor cortex, medial prefrontal cortex, and reduced GLX to creatine-phosphocreatine ratios (a proxy measure of neuronal excitability) in the posterior cingulate, overlapping with the regions reported here in the VBM analyses. 35 In line with the guidelines of Pell and colleagues 36 on maximization of detection power in group comparison VBM, our control group size varied across analyses. However, a subset of participants was kept constant across all 3 analyses.…”
Section: Neuropsychological and Brain Region Relationshipsmentioning
confidence: 98%
“…For example, studies using voxel-based analyses found topographical abnormalities in frontal cortical gray matter (GM) concentration and volume [3][4][5]. Moreover, studies using diffusion tensor imaging (DTI) or magnetic resonance spectroscopy (MRS) analyses observed changes in white matter (WM) and GM connectivity that indicated abnormal function within the thalamofrontal network in JME patients [6,7]. An emphasis on abnormal function in the frontal lobe of JME patients Seizure 30 (2015) [124][125][126][127][128][129][130][131] was reinforced by findings from neuropsychological testing [8] and EEG analyses [9], but several recent studies have also identified extra-frontal, focal cortical, and regional abnormalities [4,10].…”
Section: Introductionmentioning
confidence: 97%